Testing Open-Air Storage of Stumps to Provide Clean Biomass for Energy Production - Luigi Pari; Antonio Scarfone; Vincenzo Alfano; Simone Bergonzoli; Francesco Gallucci; Enrico Santangelo (Energies, 2017)
When orchards reach the end of the productive cycle, the stumps removal becomes a mandatory operation to allow new soil preparation and to establish new cultivations. The exploitation of the removed stump biomass seems a valuable option, especially in the growing energy market of the biofuels; however, the scarce quality of the material obtained after the extraction compromises its marketability, making this product a costly waste to be disposed. In this regard, the identification of affordable strategies for the extraction and the cleaning of the material will be crucial in order to provide to plantation owners the chance to sell the biomass and offset the extraction costs. Mechanical extraction and cleaning technologies have been already tested on forest stumps, but these systems work on the singular piece and would be inefficient in the conditions of an intensive orchard, where stumps are small and numerous. The objective of this study was to test the possibility to exploit a natural stumps cleaning system through open-air storage. The tested stumps were obtained from two different vineyards, extracted with an innovative stump puller specifically designed for continuous stump removal in intensively-planted orchards. The effects of weathering were evaluated to determine the fuel quality immediately after the extraction and after a storage period of six months with respect to moisture content, ash content, and heating value. Results indicated interesting storage performance, showing also different dynamics depending on the stumps utilized.